STRATEGI PEMBELAJARAN PAI BERDIMENSI PENDIDIKAN MULTIKULTURAL (STUDI KASUS PEMBELAJARAN PAI DI SMPN 1 PILANGKENCENG) (KUTTAB, 2024)
To maintain national unity, education is essential for both national and international life. Indonesia is a multicultural country with diverse ethnicities, tribes, races, cultures, and religions. This research focuses on understanding how Islamic Religious Education (PAI) is developed based on multicultural education at SMPN 1 Pilangkenceng. This qualitative study involves a PAI teacher at SMPN 1 Pilangkenceng. The results indicate that PAI education should be developed with multicultural considerations at SMPN 1 Pilangkenceng. The school employs both expository and inquiry strategies, emphasizing the material presented by the teacher and including activities that encourage questioning during learning and teaching processes. In the implementation of PAI teaching based on multicultural education, the PAI teacher at SMPN 1 Pilangkenceng also involves non-Muslim students in certain topics, while excluding them from other topics related specifically to Buddhism and other religions.